Acute osimertinib exposure induces electrocardiac changes by synchronously inhibiting the currents of cardiac ion channels - Li, Peiwen; Tian, Xiaohui; Wang, Gongxin; Jiang, Enshe; Li, Yanming; Hao, Guoliang (Frontiers in Pharmacology, 2023)
As the third generation of epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI), Osimertinib demonstrated more significant cardiotoxicity than the previous generations’ EGFR-TKIs. Investigating the mechanism of osimertinib cardiotoxicity can provide a reference for a comprehensive understanding of osimertinib-induced cardiotoxicity and the safety of drug usage in clinical practice. Multichannel electrical mapping with synchronous ECG recording was used to investigate the effects of varying osimertinib concentrations on electrophysiological indicators in isolated Langendorff-perfused hearts from guinea pigs. Additionally, the whole-cell patch clamp was used to detect the impact of osimertinib on the currents of the hERG channel transfected on the HEK293 cells, the Nav1.5 channel transfected on the Chinese hamster ovary cells and the acute isolated ventricular myocytes from SD rats. Acute exposure to varying osimertinib concentrations produced the prolongation in the PR interval, QT interval and QRS complex in isolated hearts from the guinea pig. Meanwhile, it could concentration-dependently increase the left atrium, left ventricle and atrioventricular conduction time without affecting the left ventricle conduction velocity. Osimertinib inhibited the hERG channel with IC50 of 2.21±1.29 μM in a concentration-dependent manner. Osimertinib also concentration-dependently inhibited the Nav1.5 channel for which the IC50 value in the absence of inactivation, 20% inactivation and 50% inactivation were 15.58±0.83 μM, 3.24±0.09 μM, 2.03±0.57 μM respectively. Osimertinib slightly inhibited the currents of L-type Ca2+ channels in a concentration-dependend mode in acute isolated rat ventricular myocyte. It was concluded that osimertinib could prolong QT interval, PR interval, QRS complex, left atrium and left ventricle and atrioventricular conduction time in isolated guinea pig hearts. Further, osimertinib can block the hERG, Nav1.5 and L-type Ca2+channels in a concentration-dependent manner. Therefore, it might be the leading cause of its cardiotoxicity effects, such as QT prolongation, decreased left ventricular ejection fraction.